The Influence of the SQ4R Learning Model with Digital Schoolbooks on Students' Understanding of Biology Concepts - Rahman Subandi; Vandalita M.M. Rambitan; Makrina Tindangen; Sri Purwati (Universitas Islam Negeri Walisongo Semarang, 2023)
The low understanding of concepts can be caused because the learning process is not maximized which makes students inactive, unable to think independently, more practical to find answers on the internet, and unable to express what they have learned. Digital School Books as a medium and learning model Survey, Question, Read, Reflection and Review (SQ4R) is an alternative that can activate students and make it easier to remember concepts so that learning is more meaningful. The purpose of this study was to describe the effect of the SQ4R learning model with digital school books on students' understanding of biology concepts in class VII at the Madrasah Tsanawiyah Nurussa'adah Sangkulirang Islamic Boarding School. This research is a quasi-experimental study with a pretest-posttest control group design. The study population was students of class VII, using cluster random sampling technique which produced class VII.B as the experimental class and class VII.A as the control class. The results of the data analysis showed that there was an influence of the SQ4R learning model with digital school books on the understanding of biology concepts for class VII students at the Madrasah Tsanawiyah Nurussa'adah Sangkulirang Islamic Boarding School.